Metal–Organic Framework-Based Catalysts: Chemical Fixation of CO2 with Epoxides Leading to Cyclic Organic Carbonates - Beyzavi, M. Hassan; Stephenson, Casey J.; Liu, Yangyang; Karagiaridi, Olga; Hupp, Joseph T.; Farha, Omar K. (Frontiers in Energy Research, 2015)
As a C1 feedstock, CO2 has the potential to be uniquely highly economical in both a chemical and a financial sense. In particular, the highly atom-economical acid-catalyzed cycloaddition of CO2 to epoxides to yield cyclic organic carbonates (OCs), a functionality having many important industrial applications, is an attractive reaction for the utilization of CO2 as a chemical feedstock. Metal–organic frameworks (MOFs) are promising candidates in catalysis as they are a class of crystalline, porous, and functional materials with remarkable properties including great surface area, high stability, open channels, and permanent porosity. MOFs structure tunability and their affinity for CO2, makes them great catalysts for the formation of OCs using CO2 and epoxides. In this review, we examine MOF-based catalytic materials for the cycloaddition of carbon dioxide to epoxides. Catalysts are grouped based on the location of catalytic sites, i.e., at the struts, nodes, defect sites, or some combination thereof. Additionally, important features of each catalyst system are critically discussed.